Is the guaranteed health care coverage for long-term nursing home care considered limited by the payer of the National Health Fund? - Stasiak, Elżbieta; Stasiak, Karolina; Stasiak, Łucja; Deluga, Alina; Wasil, Anna (Journal of Education, Health and Sport, 2017)
The elderly person in the geriatric age, and thus very often with a disability, is too sparingly provided with holistic health care services in the home environment. One of the forms, which operates in the market of health care services and which is dedicated to the elderly and disabled is a long-term home-based nursing care. For over 17 years the market for health care services has been organized and led by nurses who are an independent professional group and whose actions have been based on the contracts with the National Health Fund. Despite the ever increasing demand for this type of care, the payer or the National Health Fund treats these benefits as limited. These benefits are for the payer the cheapest form of care addressed to the elderly and disabled. In view of the fact that Polish society is aging at a rapid rate and is thus faced with multiple morbidities, these health benefits should be guaranteed and unlimited. This change would bring huge savings in health care. Due to the insufficient number of places, the person who is eligible for long-term home-based nursing care is put on a waiting list.